Knowledge, attitude, and practice regarding COVID-19 pandemic among medical students of Ernakulam, India - Jacob Davies Kalliath; Anuradha Kizhatil; Brilly M Rose; Ann Mary Kuncheria; Alexander John (Journal of Ideas in Health, 2021)
Background: COVID – 19 infection is a serious pandemic the world is now facing. This study aimed to assess the knowledge, attitude, and practice regarding COVID-19 infection among medical students at a private medical college in central Kerala.